2019
DOI: 10.1021/acs.jmedchem.9b01540
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Structural Determinants of Inhibitor Affinity and Selectivity in Complexes with Histone Deacetylase 6

Abstract: Inhibition of histone deacetylase 6 (HDAC6) has emerged as a promising therapeutic strategy for the treatment of cancer, chemotherapy-induced peripheral neuropathy, and neurodegenerative disease. The recent X-ray crystal structure determination of HDAC6 enables an understanding of structural features directing affinity and selectivity in the active site. Here, we present the X-ray crystal structures of five HDAC6-inhibitor complexes that illuminate key molecular features of inhibitor linker and capping groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 60 publications
0
57
0
Order By: Relevance
“…Recently, one of the most active and selective oxazole derivatives published by Senger et al (IC 50 = 0.06 μM on HDAC6, IC 50 = 14 μM on HDAC1 and HDAC8) JS28 (41, Figure 3), which is similar to compound 38 but has a para-bromophenyl substitution on the oxazole hydroxamic acid, has been co-crystallized with zebrafish HDAC6 (PDB ID: 6Q0Z). [75,76] The solved crystal structure of JS28 corresponded to the predicted binding mode obtained by molecular docking into the homology model of human HDAC6 (RMSD 0.8 Å). Namely, the hydroxamic acid chelates the zinc ion in a bidentate manner and undergoes hydrogen bonds with the side chains of the nearby conserved amino acid residues H573, H574 and Y745.…”
Section: Optimization Of the Linkermentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, one of the most active and selective oxazole derivatives published by Senger et al (IC 50 = 0.06 μM on HDAC6, IC 50 = 14 μM on HDAC1 and HDAC8) JS28 (41, Figure 3), which is similar to compound 38 but has a para-bromophenyl substitution on the oxazole hydroxamic acid, has been co-crystallized with zebrafish HDAC6 (PDB ID: 6Q0Z). [75,76] The solved crystal structure of JS28 corresponded to the predicted binding mode obtained by molecular docking into the homology model of human HDAC6 (RMSD 0.8 Å). Namely, the hydroxamic acid chelates the zinc ion in a bidentate manner and undergoes hydrogen bonds with the side chains of the nearby conserved amino acid residues H573, H574 and Y745.…”
Section: Optimization Of the Linkermentioning
confidence: 97%
“… [74c,85] A number of these highly selective as well as several less selective inhibitors and compounds with undetermined selectivity of the same chemotype were co‐crystallized with zebrafish HDAC6: nexturastat A (PDB IDs: 5G0I, 5G0J), HPOB (PDB ID: 5EF7), HPB (PDB ID: 5WGK), peptoid‐based inhibitors ( 6 and others, PDB IDs: 6DVL, 6DVM, 6DVN), ACY‐1083 (PDB ID: 5WGM), bavarostat (PDB ID: 6DVO), imidazopyridine derivative MAIP‐032 (PDB ID: 6CGP), phenothiazine derivative KV70 (PDB ID: 5W5K), dual HDAC‐proteasome inhibitor RTS‐V5 ( 68 , PDB ID: 6CW8), broad‐spectrum HDAC inhibitor AR‐42 ( 69 , PDB IDs: 6UO3, 6UO5, 6UO7), givinostat ( 70 , PDB ID: 6UOC), bishydroxamic acid ( 71 , PDB ID: 6VNR) and diverse inhibitors (compounds 72 – 74 , PDB IDs: 6PZO, 6PZS, 6PZU; Figure 4). [18g–i,76,85h,j,86] The experimentally obtained binding modes shed light on the protein‐ligand interactions and structure–activity relationships of these compounds. Strikingly, and in contrast to typically observed bidentate binding of hydroxamic acids with alkyl and vinyl linkers, all listed benzhydroxamic acids are bound in a monodentate fashion except bavarostat ( 63 ), AR‐42 ( 69 , PDB ID: 6UO3) and givinostat ( 70 ).…”
Section: Strategies To Design Selective Hdac Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, crystal structures of drHDAC6 in complex with hydroxamic acid derivatives have shown that the inhibitors can chelate the catalytic zinc ion in either mono-or bidentate fashion. 54,[80][81][82][83] Hence, two different settings were used for docking of the hits into HDAC6 structure to investigate plausible binding modes.…”
Section: Compoundmentioning
confidence: 99%
“…Further preparations of the protein structures were done using the Protein Preparation Wizard of Schrödinger software. 82,96 Bond orders were assigned and hydrogen atoms added, and the H-bond network was subsequently optimized. The protonation states at pH 7.0 were predicted using the Epik-tool in Schrödinger.…”
Section: Fret Assaymentioning
confidence: 99%